Jomon pottery: cord-imitating decoration - Zhushchikhovskaya, Irina (Documenta Praehistorica, 2007)
The paper discusses the decoration of pottery of the Neolithic Jomon culture (Japanese Archipelago, 13600-900 BC). The comb-impressed pattern produced by various kinds of cord or rope stamps is considered as the "calling card" of Jomon pottery from the earliest cultural periods to the latest. Another kind of decoration recognized recently uses the cord not as a patterning tool, but as an essential motif of decorative composition. High relief elements imitate cordage forms and structures - knots, loops, hanging cord, net, etc. This kind of decoration corresponds to the pottery of Mid- dle Jomon period (3500-2500 BC) sites located in northern and north-eastern Honshu and southern Hokkaido. It is supposed that the introduction of images of real material object into the field of decorative art was reasoned by the meaning of cord and cordage as cultural signs during the Middle Jomon period. Interesting parallels to some cordage structures reconstructed on Middle Jomon pottery decoration are well known in traditional Japanese culture of VI-XX cc. Analytical interpretation of this resemblance may became the subject of special research.
Keywords: Japonska; arheološke najdbe; ceramic; keramika; okrasni predmeti; vzorci